An evaluation of the use of immunoglobulin A antibody response against mycobacterial antigens for the diagnosis of Mycobacterium bovis infection in cattle. (May 2015) - Jeon, Haet Sal; Shin, A-Rum; Son, Yeo-Jin; Kim, Jae-Myung; Jang, Yunho; Kim, Suk; Lee, Kang-In; Choi, Chul Hee; Park, Jeong-Kyu; Kim, Hwa-Jung
Antibody responses are useful indicators of Mycobacterium bovis infection in cattle. Many studies have evaluated the ability of immunoglobulin G (IgG) to serodiagnose bovine tuberculosis (TB). In the current study, immunoglobulin A (IgA) and IgG responses against the MPB70 and MPB83 antigens of M. bovis, the 38 kDa phosphate-binding lipoprotein (PstS1) that is a well-known serodiagnostic M. tuberculosis antigen, and a newly identified protein, termed Rv1483c, were compared in M. bovis –infected and noninfected cattle as well as in field samples. The diagnostic utility of the IgA antibody to MPB70 and MPB83 for bovine TB was superior or comparable to that of the IgG antibody, and the sensitivity of serodiagnosis increased when the results of antigen binding by IgA and IgG were combined. The sensitivities of the IgG and IgA antibodies to the Rv1483c and PstS1 proteins were significantly lower than those to MPB70 and MPB83, and no diagnostic utility for Rv1483c was observed in field samples. Importantly, the IgA antibody reacted strongly to the MPB70 and MPB83 antigens and differentiated cattle with TB from healthy cattle in a multiantigen printed immunoassay. The results of this study support the feasibility of using IgA antibody against the MPB70 and MPB83 antigens to detect bovine TB. In addition, approaches using assays for both IgA and IgG antibodies may increase detection accuracy.